Habitat ecology, structure influence diversity, and host-species associations of wild orchids in undisturbed and disturbed forests in Peninsular Malaysia - Besi, Edward Entalai; Mustafa, Muskhazli; Seok, Christina Yien Yong; Go, Rusea (Multidisciplinary Digital Publishing Institute, 2023)
As an attempt to examine the causes of forest disturbance and degradation of the orchid community, a comparative study on diversity and ecology in eight undisturbed and ten disturbed forests in Peninsular Malaysia was conducted that varied in areas, elevations, vegetation types, and disturbance regimes. Density and individual-based rarefaction curves were used to describe the abundance. Univariate and multivariate analyses were also performed to explore the associations of species abundance with biotic and abiotic factors. The study reported 239 orchid species belonging to 65 genera. Species richness, abundance, density, and diversity of orchids varied by locality. Higher density of orchids (2.433 plants/km2) occurred in the undisturbed forests than in the disturbed forests (0.228 plants/km2). As with the character of undisturbed forests, the temperature was between 27.8 ± 0.3 °C and 31.2 ± 0.2 °C, humid (77.1 ± 1.2%–89.6 ± 0.9%), and with low light intensity (23.8 ± 3.3 μmol m−2s−1–171.7 ± 18.8 μmol m−2s−1), thus supporting the high density of the plants. Disturbed forests had higher diversity (H = 4.934 and 1-D = 0.990) and abundance (183 species of 57 genera) but were determined to be highly influenced by the higher abundance of epiphytic orchids on the fallen trees and ease of accessibility in the logged forests. Terrestrial and mycoheterotroph orchids were much lower in density and abundance in the disturbed habitat indicating a gradual reduction in their niche availability following the disturbance. Additionally, the ecology data show that the microclimate conditions of the canopy-covered forest was influenced by proximity to the logged area which had eventually reduced the orchids’ habitat quality. Furthermore, the results show that the abundance of epiphytic orchid communities was associated with the host plant characteristics. Host types and bark texture preference were apparent for the epiphytic orchid species, with certain types and textures hosting more orchid species than others. Overall results show that extreme temperature, humidity, and light intensity caused by the canopy opening inflicted damages to the habitat conditions and bark textures of the host plants and limits recolonisation of the orchids in the disturbed forests. The species diversity and density patterns of orchids in undisturbed and disturbed forests revealed in this study provide a baseline for conservationists, policy makers, and forest authorities in expanding the understanding of the forest ecology and vegetation along the disturbance gradient, forest regeneration, and criteria for plant selection for forest restoration in Peninsular Malaysia.